Academic Stress Level Determination among College Students in Times of Covid-19 Pandemic: Basis for an Intervention Scheme - Rodrigo Jr Licayan; Funa, Mary Chierife C; Lagatiera, Gary P; Cabeza, Robert Kim (International Journal of Asian Education, 2021)
This study measured the level of academic stress among students regarding personal inadequacy, fear of failure, interpersonal difficulties with teachers, and inadequate learning resources in times of Covid-19 pandemic Using a descriptive-comparative approach. Slovin's formula was used to identify the respondents with a stratified random sampling technique to generate the required sample size of the study. The results revealed that the level of academic stress in times of the Covid-19 pandemic is high. It is also revealed that there is no significant difference in the level of academic stress when respondents are grouped according to sex, year level, and the number of hours spent for modular learning per day and provided significant difference when grouped according to course. Demographic profiles show that most of the students belong to the poor classification of monthly family income and with a low allowance for internet subscriptions. It also shows that with the intensity of requirements in the course pack, most students allocated many hours to answer the lessons per day. Present findings suggest that the institution must address intervention schemes through academic and non-academic services.